ANALISIS MINAT SISWA TERHADAP PELAJARAN MATEMATIKA DAN KEMAMPUAN MENYELESAIKAN MASALAH MATEMATIKA - Dewi - Kartikasari (MEJ (Mathematics Education Journal), 2017)
This minor thesis aims to determine whether or not a significant influence anatara student interest and student's ability in solving mathematical problems in class VIII MTsN Karangrejo Tulungagung. The method used in this thesis is a qualitative approach - quantitative and descriptive study. Alar analysis used is descriptive analysis and correlation using Spearman correlation. Based on the results of the discussion showed that: (1) the level of interest in learning mathematics eighth grade students MTsN Karangrejo Tulungagung in the medium category, it is shown on the third indicator of interest are two indicators shows the results being, (2) ability of solving math students in both categories, it is shown from the results of the students' work is based on four indicators Polya get a range of values in both categories, (3) while for relations interest in learning and the ability to problem-solving mathematics were analyzed using spearman correlation correlation values 0.414 with significance of 0.000 which indicates that the relationship between the interest and ability to solve problems in mathematics has a moderate correlation